Analısıs Kemampuan Membaca Permulaan Kelas 1 Sekolah Dasar dı Masa Pandemı - Ai Resti, Ai Resti; Indihadi, Dian; Saputra, Erwin Rahayu (Elementary Teacher Education Program, Majalengka University, 2023)
The purpose of this study was to determine the ability to read early, the inhibiting and supporting factors of students in early reading, and to find out the concepts applied by the school in teaching early reading, grade 1 students at SDN Gunungsari. The reason for doing this research is by the author's desire to determine the ability to read beginning in grade 1 SDN Gunungsari. The method used in this research is descriptive qualitative by using data collection techniques in the form of observation, interviews, documentation and tests. The validity of the data using triangulation. The results showed that 1) The students' reading ability was still stated to be lacking because of the total 60 students there were still 50% whose reading abilities were less or not yet fluent in initial reading. 2) the factor of the low reading ability of the first graders of SDN Gunungsari due to lack of attention and guidance from parents, so that the students' lack of interest in learning 3) the concept applied by the first grade teacher of SDN Gunungsari is only the teacher provides guidance every day by providing one word reading with how to separate as syllables.